Growth and Welfare under Endogenous Lifetime - Maik Schneider; Ralph Winkler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Welfare aspects of longevity increases are often discussed neglecting the complex relationship between longevity and economic growth, which is the focal point of another literature. Combining both perspectives, we develop an endogenous growth OLG-framework to investigate how longevity affects economic growth and welfare. In our model, life expectancy is determined endogenously by individuals' investments in healthcare. In our benchmark specification growth effects are small, but direct welfare gains from longer lifetimes can be substantial. In the generalized model specification the growth effect dominates and may even lead to overall welfare losses from longevity increases. We interpret our results with respect to real world data and discuss the importance of assumptions about the engine of growth as well as the externalities associated with healthcare investments.
Keywords: O10; I10; J10; 330